TECHNICAL PREPARATION FOR THE C.P.A. EXAMINATION. - Greene, Howard F. (The Accounting Review, 1935)
Many volumes have been written covering the material which must be studied and reviewed in preparation for sitting for the Certified Public Accountant examination. Suffice it to say that the only intelligent preparation for such an examination requires the most complete study and review of accounting theory which can possibly be undertaken. Much less material is available, however, on the technical preparation for the culmination of many months of hard labor and sacrifice. The candidate should be thoroughly sure in his own mind of the strategy to be employed before he starts. This refers to the entire examination as well as to the individual problems. For the nervous individual a relaxation period of five minutes may be desirable before starting to work. Five minutes of gazing into space with the examination papers upside down on the table is a marvelous test of self-control, and provides opportunity for the nervous candidate to realize that this examination is given twice a year, and can be taken in many states twice for the same fee. He is then in a much improved position to exert every effort logically and directly towards the achievement of his Great Desire.